Dispersion properties of surface waves at planar structures ‘metal – dielectric – magnetized plasma’ - Akimov, Yu.A.; Azarenkov, N.A.; Olefir, V.P. (Вопросы атомной науки и техники, 2002)
This report is devoted to the investigation of the dispersion properties and field spatial structure of potential surface waves (SWs) that propagate along interfaces metal – dielectric – magnetized plasma of a finite pressure. The external steady magnetic field is directed perpendicularly to the interfaces of mediums. Plasma is considered in the hydrodynamic approach as warm collision medium. The influence of finite metal conductivity, dielectric parameters, electron collision frequency and external magnetic field value on properties of the SW is investigated. The influence of the mentioned above parameters on frequency region of SW existence and spatial wave field structure is studied.